Komunikasi Dakwah Pesantren Tradisional - Rahman, Taufik (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2016)
Â Â Â Â Â Â Â Â This research is motivated by empirical data, the potential for problems in the field with regard to the growing problem of propaganda in the spread of Islam. Deployment is meant as the spread of Islam through the study of classical texts, recitals in taklim to male and female students who live in boarding Bustanul Wildan as well as to the communities in surrounding and also spread through the typical tradition traditional pesantren like tahlilan, berzanji, Rajaban, Muludan and other events. Pesantren Bustanul Wildan be of interest to researchers as objects related research. Â Â Â Â Â Â Â Â Â Research conducted at the Islamic Schools Bustanul Wildan. The paradigm used in this study is a constructivist paradigm (qualitative). constructivist paradigm, uses the case study method. The conclusions of this research are: First, Pesantren Bustanul Wildan in the spread of Islam that is the communication patterns of action, interaction and transaction. Keywords: Communication, Pesantren, Preaching Islam